Memelihara Kesehatan Dalam Perspektif Profetik - Adliah, Adliah; Muchtar, M. Ilham (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article discusses the maintenance of health in a prophetic perspective, which is based on the teachings and example of the Prophet PBUH. Health in Islam includes not only physical, but also mental and spiritual aspects, which are interrelated. The Prophet PBUH gave complete instructions on how to maintain the health of the body and soul, such as a balanced diet, regular exercise, adequate sleep, and maintaining liver hygiene. His teachings also emphasize the importance of not overeating, choosing healthy foods, and maintaining peace of mind to prevent stress. In modern life filled with health challenges, the implementation of the teachings of the Prophet PBUH has become very relevant. Unhealthy lifestyles, lack of physical activity, and high stress increasingly dominate daily life. Therefore, by following the guidance of the Prophet, Muslims can achieve balanced health and a better quality of life. These prophetic teachings provide comprehensive solutions to maintain physical and spiritual health, as well as improve the quality of life, both in this world and in the hereafter. This article aims to provide a deeper understanding of how to maintain health by following the instructions of the Prophet PBUH in daily life.